Examining the Regulatory Frameworks Governing Prohibition of Torture in Warfare - Nnawulezi, Uche; Mohammed, Safiyyah Ummu; Adiyatma, Septhian Eka; Ojekunle, Ademola O.; Ajayi, Oluwatobiloba Ifedolapo (Jurnal Media Hukum, 2000)
The aim of the paper is to examine the regulatory frameworks governing the prohibitions of torture in warfare to determine their adequacy in protecting civilian populations against torture during armed hostilities. To address the threat posed by torture in warfare against the civilian populations, the regulatory frameworks on International Humanitarian Law (IHL), International Human Rights Law (IHRL) and International Criminal Law (ICL) are examined. It may be argued that although this regulatory framework is aimed at guaranteeing safety of the civilian populations in situations of armed hostilities but are not capable of dealing with the current challenges. The paper employs a doctrinal approach by identifying and analyzing the applicable rules of IHL, IHRL, and ICL. It demonstrates how these laws impact the basic rights of civilian populations during armed conflicts. The paper found that despite the performance of the Tribunals as regulatory measures, they are confronted with several challenges prosecution and enforcement of their decisions. The paper concludes with recommendations that are relevant to address the challenges in order to ensure that the various frameworks are effectively implemented by States to safeguard the civilian populations from acts of torture during armed hostilities.